SALES INFORMATION SYSTEM AT PANCORAN 7 LABUAN BAJO RESTAURANT - Pooja Delika Luro Kale Syayu; Siswohadi Siswohadi; Andrik Gastri Widjatmiko (CV Pena Jaya Pers, 2024)
This study focuses on the development of the information exchange system for Labuan Bajo's Makan Pancoran 7 building. The main goal of the study is to design and implement an information system that can increase operational efficiency and the accuracy of transaction processing in the aforementioned makan. The methodology used in this study includes requirements analysis, system penetration testing, system implementation, and system evaluation. Descriptive qualitative approach, the data collection techniques used are observation and interviews. The data used is in the form of information related to the sales process flow, organizational structure, as well as the vision and mission of pancoran 7 labuan bajo restaurant. The data analysis technique used is qualitative data analysis technique, the stages in the analysis are data reduction, data display, conclusion and verification. Information systems for sales that are implemented include inventory management, sales tracking, order processing, and inventory management. To facilitate data access and handling, web-based pendekatan is used in system development. The research findings indicate that the implementation of this information selling system has improved the operational efficiency of the restaurant, reduced the amount of waste that is produced, and accelerated the sale process